Design and validation of a low cost, high-capacity weighing device for wheelchair users and bariatrics. - Sherrod, Brandon A.; Dew, Dustin A.; Rogers, Rebecca; Rimmer, James H.; Eberhardt, Alan W. (Assistive Technology)
Accessible high-capacity weighing scales are scarce in healthcare facilities, in part due to high device cost and weight. This shortage impairs weight monitoring and health maintenance for people with disabilities and/or morbid obesity. We conducted this study to design and validate a lighter, lower cost, high-capacity accessible weighing device. A prototype featuring 360 kg (800 lbs) of weight capacity, a wheelchair-accessible ramp, and wireless data transmission was fabricated. Forty-five participants (20 standing, 20 manual wheelchair users, and five power wheelchair users) were weighed using the prototype and a calibrated scale. Participants were surveyed to assess perception of each weighing device and the weighing procedure. Weight measurements between devices demonstrated a strong linear correlation (R2 = 0.997) with absolute differences of 1.4 ± 2.0% (mean±SD). Participant preference ratings showed no difference between devices. The prototype weighed 11 kg (38%) less than the next lightest high-capacity commercial device found by author survey. The prototype’s estimated commercial price range, $500–$600, is approximately half the price of the least expensive commercial device found by author survey. Such low cost weighing devices may improve access to weighing instrumentation, which may in turn help eliminate current health disparities. Future work is needed to determine the feasibility of market transition.